Pengaruh Kepesertaan PBI BPJS Kesehatan terhadap Risiko Catastrophic Health Expenditure di Desa Sumpang Mango - Ardi Syanjaya; Sandi Lubis; Irwan Irwan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Catastrophic Health Expenditure (CHE) is an important indicator for assessing the effectiveness of financial health protection, particularly in safeguarding households from excessive health-related expenditures. In Indonesia, the Contribution Assistance Program (PBI) of BPJS Kesehatan is designed as a social protection instrument for poor and vulnerable populations, especially those living in rural areas. This study aims to analyze the effect of PBI membership on the risk of experiencing CHE among households in Sumpang Mango Village. The study employs a quantitative explanatory approach with a cross-sectional design, in which households participating in the PBI program serve as the unit of analysis. Data were collected through a household survey and analyzed using binary logistic regression with the assistance of SmartPLS 3. The analysis also incorporates household income, household size, and health service utilization as control variables. The findings indicate that PBI membership has not been fully effective in significantly reducing the risk of CHE. In contrast, household size and the utilization of health services have a positive and significant effect on the likelihood of experiencing CHE. Meanwhile, household income does not show a significant association with CHE risk. These findings suggest that financial health protection at the village level is not determined solely by health insurance coverage but is also influenced by household structural characteristics and patterns of health service utilization. Therefore, strengthening social protection policies that are more responsive to local conditions and needs is essential to reducing the risk of CHE in rural communities.